Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1029/2023sw003480
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Ionospheric Modeled TEC in the Equatorial Ionosphere During the 2013 March and 2021 November Geomagnetic Storms

Abstract: This paper presents the validation of modeled total electron content (TEC) from 14 ionospheric models, including empirical, physics‐based, and data assimilation (DA) models, hosted by the NASA/NSF Community Coordinated Modeling Center (CCMC), NOAA Space Weather Prediction Center, and NASA Jet Propulsion Laboratory (JPL). This study aims to assess the current progress and capability of the CCMC‐hosted ionospheric models in capturing the storm time ionosphere during the low and moderate solar flux years. We focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…This may explain why the model had greater success in predicting WSPR links during the day than at night, since larger values of NmF2 are more conducive to ground-to-ground HF propagation and our test is inherently one-sided (i.e., it does not account for "false positive" propagation predictions). We note that other validation studies of SAMI3 covering different periods have not uncovered the same positive bias, for example, Chou et al (2023) found SAMI3 had a normalized skill score of 0.95-1 for mean TEC error in two storms, indicating the model was essentially unbiased. Further study would be required to determine whether this is due to the chosen periods of study, or to the choice of validation parameter (TEC vs. NmF2).…”
Section: Discussionmentioning
confidence: 63%
“…This may explain why the model had greater success in predicting WSPR links during the day than at night, since larger values of NmF2 are more conducive to ground-to-ground HF propagation and our test is inherently one-sided (i.e., it does not account for "false positive" propagation predictions). We note that other validation studies of SAMI3 covering different periods have not uncovered the same positive bias, for example, Chou et al (2023) found SAMI3 had a normalized skill score of 0.95-1 for mean TEC error in two storms, indicating the model was essentially unbiased. Further study would be required to determine whether this is due to the chosen periods of study, or to the choice of validation parameter (TEC vs. NmF2).…”
Section: Discussionmentioning
confidence: 63%
“…The objective of this section is to investigate the impact of the E × B velocity term on the inversion of density, velocity, and temperature during the geomagnetic storm. Different from quite solar period on 23 Dec 2019 in previous section, we select a geomagnetic storm event driven by coronal mass ejections, focusing on the SAMI3 simulation data on 4 Nov 2021 (Chou et al, 2023). Therefore, the SAMI3 simulation parameters at time 00 : 00: 00 ∼00 : 15: 00 on 4 Nov 2021 have been chosen as follows: F10.7 A = 87.8024, F10.7 = 90.8000 (every 24 hr), Ap = 94 (every 3 hr), Kp = 6 (every 3 hr).…”
Section: Pinn-sami3 Framework Test During a Geomagnetic Stormmentioning
confidence: 99%
“…An example of a physics‐based data assimilation model is the Whole Atmosphere Model‐Ionosphere Plasmasphere Electrodynamics (WAM‐IPE), which is operated at the National Oceanic and Atmospheric Administration Space Weather Prediction Center. This model utilizes a wealth of ground‐based and space‐based observations, solar activity indices, geomagnetic data, and lower atmospheric forcing (Chou et al., 2023; Fang et al., 2022), making it valuable for characterizing and predicting the behavior of the ionosphere during space weather events. Nonetheless, the complexity and computation time required for the operation of data assimilation models still pose challenges.…”
Section: Introductionmentioning
confidence: 99%